PENDIDIKAN, HOMINISASI DAN HUMANISASI - DARDIRI, ACHMAD (Universitas Negeri Yogyakarta, 2005)
Theoritically and ideally, education is an attempt to humanize human beings. This implies that teachers, lectures, tutors or instructors have to realize it when they are dealing with children (or learners. However. in practice, the opposite sometimes, or even rr/ten, takes place. The dehumanization of children or learners occurs through ways of teaching rhea are authoritarian, distressing, frightening and through other ways not conducive to attempts to develop humanistic potencials. In the context of rduuuion, (in attempt to humanize human beings can be culled the humanization of children or learners. The meaning of humanism in this context can be seen, explicitly or implicitly, as the views from some figures that this article talks about.